When the Movie Screen Becomes An “Emotional” Narrative Within the Family (Film Analysis of NKCTHI) - Dea Fiqri Amalia; Khaerudin Imawan (Indonesian Journal Publisher, 2025)
The film Nanti Kita Cerita Tentang Hari Ini (NKCTHI), or We'll Talk About Today Later, depicts emotional communication within families through symbols, expressions, and visual atmospheres by revealing the denotative meanings, connotations, and myths in each scene depicting emotional communication within the family, as well as understanding how viewers interpret the messages conveyed in the film using a participatory approach with descriptive qualitative methods. Content analysis was conducted on ten scenes and supported by viewer interviews and literature reviews. The results of the study show that the film (NKCTHI) depicts the dynamics of emotional communication such as loss, inner pressure, conflict, and the healing process. The audience interprets each scene in the film differently, influenced by their respective experiences and emotional backgrounds. Films can be a medium that reflects patterns of emotional communication in modern families